Research Article Perekonomian Provinsi-Provinsi di Indonesia Pasca Terdampak Gempa Bumi - Zaky Musyarof; Indira Nur Qomari (FEB Universitas Sultan Ageng Tirtayasa, 2022)
Earthquake is a large-scale natural disaster that still very difficult to predict precisely and accurately. Experts have not been able to predict when, where, and how strong an earthquake will occur. Earthquake that are often sudden and without obvious signs causes a huge impact if hit a populated area. Infrastructure damages and casualties are inevitable. This condition directly causes massive economic losses. Facilities and infrastructure damages, and labor loss are the main factors that detain the economy. Post-disaster reports by vatious agencies present losses up to millions of US dollar. However, even though each region affected by earthquake suffered massive economic losses, not all of them affected significant impacts on GDP/GRDP and economic growth of the regions. A number of studies had stated that a number of countries economies did not affected by earthquakes. Then, what about regions in Indonesia that are often hit by earthquakes? This research tries to find out about that. Case studies were taken on eleven major earthquakes from 1992 to 2018. GRDP and economic growth of provinces affected by earthquakes compared between before and after earthquake. Analytical methods used in this research are compare means and forecasting. With the scale of research at provincial level, the result shown that there were provinces able to restored their economies after an earthquake, reflected in GRDP and economic growth of those provinces that had not changed after earthquakes.